Analisis Penerapan Model Problem Based Learning Dalam Mengembangkan Sikap Peduli Lingkungan Siswa Pada Materi Pencemaran Lingkungan - Iseu Laelasari; Aulia Rahmawati (Symbiotic: Journal of Biological Education and Science, 2020)
The study aims to analyze the application of the model of Problem Based Learning in developing environmental concern for environmental pollution materials, as well as an obstacle factor in developing environmental concern. Researchers use library research methods with a content analysis approach. Analysis is performed on a data source of books and journals relevant to research, and researchers search for common threads to make generalization. Research indicates that application of the model for the problem based learning in environmental pollution material has a positive impact and can be a reflection of environmental concern for students. There are a number of inhibitors in developing students' ward care attitudes: (1) student continuity in interacting with the ward especially when doing outdoor learning, (2) time constraints for planting environmental worth in learning, (3) the need to be balanced for the environment in the family ward.